Examining the Impact of Digital Bureaucratic Competency and AI-Enabled Decision Support on Public Service Delivery and Administrative Responsiveness - Ahmed, Rizwan (Department of Public Administration, Parahyangan Catholic University, 2025)
In today’s digital age, equipping government agencies with the right technology is crucial to boost their overall performance. This paper looks at how digital bureaucratic competency and AI-enabled decision support affect public service quality and responsiveness in Pakistan’s public sector. Information was gathered from 423 staff members via a structured Google Form distributed through convenience sampling. The analytical framework grouped the study variables into four main blocks: digital know-how, AI application, service delivery results, and administrative responsiveness. Factor analysis confirmed the latent constructs, while regression tests measured the links between them. Results show that stronger digital skills and AI-assisted tools noticeably improve the speed and quality of public services, especially when demand is high and change is frequent. The research therefore urges deeper investments in training and AI infrastructure if for improved governance. The findings enrich ongoing debates in public administration and provide concrete guidance for policymakers who wish to build quicker, citizen-focused public services in developing countries.